The Spillovers of Employment Guarantee Programs on Child Labor and Education. (1st August 2019) - Li, Tianshu; Sekhri, Sheetal
Abstract: Many developing countries use employment guarantee programs to combat poverty. This study examines the consequences of such employment guarantee programs for the human capital accumulation of children. It exploits the phased roll-out of India's flagship Mahatma Gandhi National Rural Employment Guarantee Scheme (MGNREGA) to study the effects on enrollment in schools and child labor. Introduction of MGNREGA results in lower relative school enrollment in treated districts. It also finds that the drop in enrollment is driven by primary school children. Children in higher grades are just as likely to attend school under MGNREGA, but their school performance deteriorates. Using nationally representative employment data, the study finds evidence indicating an increase in child labor highlighting the unintentional perverse effects of the employment guarantee schemes for human capital.